ARTnet Perspectives and Contributions to Theranostics - Francis, Roslyn J.; Bailey, Dale L.; Willowson, Kathy; Latter, Melissa J.; Chappell, Bridget; McGill, George; Hofman, Michael S.; Emmett, Louise; Scott, Andrew M. (World Journal of Nuclear Medicine, 2025)
Theranostics is a rapidly growing field, providing new therapeutic options for cancer patients. Clinical trials have a key role in establishing the efficacy and safety of new treatments and determining impact on patient care. Multicenter clinical trials with radiopharmaceuticals provide robust data to support clinical implementation; however, there are important considerations to ensure high-quality and reliable clinical data.Australasian Radiopharmaceutical Trials Network (ARTnet) is a multidisciplinary clinical trials network established in 2014 to facilitate multicenter clinical trials with radiopharmaceuticals in Australia. Over the last decade, ARTnet has supported impactful, prospective clinical trials through quality activities and engagement. In theranostics, Australia has had a key role in clinical translation and generating evidence for safety and efficacy, resulting in regulatory approval and health care funding internationally. This report describes the development of ARTnet as a clinical trials network, highlighting the intent, current status, and operations of ARTnet, with a particular focus on theranostics.
Keywords: clinical trials; harmonization; oncology; radiopharmaceuticals; theranostics